Strategi Pemasaran Syariah Produk Madu Lebah UMKM Madu Kuok - Insusanty*, Enny; Novisa, Anthon (Universitas Lancang Kuning, 2025)
The aim of the research is to determine the marketing strategy of UMKM Madu KuOK using sharia concepts. The research method was carried out by survey through interviews, observation and literature study. Sharia Marketing for UMKM Madu KuOK by applying sharia marketing concepts and strategies in marketing its products, namely Teisti (Rabbaniyah), Ethical (Akhlaqiyyah), Realistic (al-waqiyyah), and Humanistic (insaniyyah). Apart from that, the marketing concept with marketing mix) was also implemented with the 4 P marketing strategy variables, namely: product, place, price and promotion.